Lethal and Sublethal effects of four essential oils on the egg parasitoids Trissolcus basalis - Werdin Gonzalez, Jorge Omar (2013)
The essential oils from leaves of Schinus molle var. areira, Aloysia citriodora, Origanum vulgare and Thymusvulgaris have showed potential as phytoinsecticides against the green stink bug, Nezara viridula. In thiswork were evaluated their toxicological and behavioral effects on the parasitoid Trissolcus basalis, a biological control agent of this pest insect. Essential oils were obtained via hydrodestillation from fresh leaves.Insecticide activity in T. basalis females was evaluated in direct contact and fumigation bioassays. Behavioral effects were evaluated in olfactometer bioassays. To evaluate the residual toxicity, females of the parasitoids were exposed to oil residues; in these insects, the sublethal effects were evaluated (potential parasitism and survivorship of immature stages). The essential oils from O. vulgare and T. vulgaris proved to be highly selective when used as fumigant and did not change parasitoid behavior. After one week, the residues of these oils were harmless and did not show sublethal effects against T. basalis. According with these results, essential oils have potential applications for the integrated management of N. viridula.